Field-Free Molecular Orientation Induced by a Single-Cycle THz Laser Pulse Train (Communications in Computational Physics, 2018)
We investigate theoretically the field-free orientation of CO molecules inducedby a single-cycle THz laser pulse train. It is shown that the molecular orientationcan be obviously enhanced by applying the pulse train. The laser intensity andpulse number have some effects on the molecular orientation. The high degree of field-freemolecular orientation $|$$〈$cos$θ$$〉$$|$max=0.9246 is obtained at temperature $T$=0 K. Thevariations of the maximum orientation degree with the experimentally available pulsenumber and peak intensity are given. Temperature $T$ has a considerable influence onthe field-free molecular orientation. The maximal field-free molecular orientation at $T$=0, 10, 20 and 30 K for $N$=14 and $E_0$=1.8 MV/cm are $|$$〈$cos$θ$$〉$$|$max=0.9188, 0.7338,0.6055 and 0.5154 in order, and the corresponding effective duration times of molecularorientation are $∆t$=0.759, 0.432, 0.297 and 0.117 ps.